The effects of Tai Chi exercise on sleep quality among the elderly: a study based on polysomnographic monitoring - Wang, Chao; Jiang, Tao; Li, Hansen; Cao, Guikang; Zhang, Guodong (Frontiers in Neurology, 2024)
Background Sleep disorders contribute to an increased risk of depression, cardiovascular issues, and various other diseases among older individuals. Consequently, enhancing the sleep quality of this demographic population has become a pressing concern. The objective of this study was to investigate the influence of an 8-week Tai Chi exercise intervention in the sleep quality of older adults. Methods Sixty individuals aged 60 years and above, recruited from the community around Southwest University in Beibei District, Chongqing City, were randomly assigned to either a control group (30 participants) or an intervention group (30 participants). The control group adhered to their normal daily routines during the 8-week experimental period, while the intervention group engaged in a 60-min Tai Chi practice three times a week for 8 weeks. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), the Insomnia Severity Index (ISI), and the Epworth Sleepiness Scale (ESS). Additionally, the Polysomnographic Sleep Quality Monitoring System (PSG) was employed to monitor the sleep process before and after the Tai Chi intervention. Results After the experiment, significant differences were observed in PSQI and IEI scores between the intervention and control groups (p < 0.05). In the experimental group, the pre-post comparisons revealed a significant increase in time spent in bed (p < 0.05), total sleep time (p < 0.05), and non-REM sleep stage 2 (p < 0.05). Conclusion The findings indicate that Tai Chi exercise may improve subjective reported sleep quality. In addition, Tai Chi exercise may alleviate general drowsiness, extend sleep duration, and optimize the sleep process and structure. Consequently, Tai Chi exercise may be a suitable exercise to improve sleep quality in older individuals.